Effects of Lapsi Choerospondias axillaris on Growth and Immune-Related Genes in Silver Carp (Hypophthalmichthys molitrix) - Shyam Narayan Labh (Ital Publication, 2020)
This study investigates the effects of Lapsi Fruit Extracts (LFE) Choerospondias axillaris (Roxburg 1832) on growth performance, haematology, biochemical with some growth and immune-related genes in silver carp fingerlings (Hypophthalmichthys molitrix). For this purpose, three hundred and seventy-five fish (5.17±0.13g) divided into six groups into eighteen aquaria and fish were fed six purified diets supplemented with ethanol extract (80%) of lapsi fruits (LFE) as A (0.0 g control), B (0.2 g), C (0.4 g), D (0.8 g), E (1.6 g), and F (3.2 g /100 g) for 90 days. Significantly higher (P<0.05) weight gain, %weight gain, SGR, and lysozyme were recorded in D (0.8 g) diet-fed group, while FCR was higher in the control diet group. In haematology, no significant differences (P>0.05) were observed among the treated and control diet-fed group while reducing trends were observed in SOD, CAT, and GPx levels as compared to control. Glucose, triglyceride, and cholesterol level were higher in control and the decreasing trend observed in continuous feeding of the LFE supplemented diet. Protein albumin and globulin level were always higher (P<0.05) in all the treated groups and was better in D (0.8 g) diet-fed group. As compared to -actin gene, growth hormone (GH), insulin-like growth factors I and II (IGF-I and IGF-II) in the liver were always higher and similar results were observed in immune‐related genes interleukin‐8 (IL-8), interleukin-10 (IL-10) and tumor necrosis factor (TNF- ) in the head kidney of silver carp. The results suggest that lapsi fruit extracts (LFE) can be useful as a feed supplement for proper growth and enhance disease resistance by improving immunity in blood, liver, and head-kidney tissues.